2022
DOI: 10.1108/ijoem-07-2021-0991
|View full text |Cite
|
Sign up to set email alerts
|

The role of education in filling the gender gap in financial inclusion in low-income economies

Abstract: PurposeThis study aims to investigate whether gender predicts financial inclusion and whether education can fill the gender gap in financial inclusion when controlling for the effects of supply side factors of financial inclusion in low-income economies.Design/methodology/approachThis study aims to investigate whether gender predicts financial inclusion and whether education can fill the gender gap in financial inclusion when controlling for the effects of supply side factors of financial inclusion in low-inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…Kumar and Pathak (2022) show that more financial awareness through education increases the level of financial inclusion. Similarly, Sharif, Naghavi, Waheed and Ehigiamusoe (2022) found that education reduces the gender gap and improves financial inclusion. Ozili (2018) argued that digital finance that is offered through Fintech providers has positive effects for financial inclusion because of the convenience that digital finance provides to individuals with low and variable income.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Kumar and Pathak (2022) show that more financial awareness through education increases the level of financial inclusion. Similarly, Sharif, Naghavi, Waheed and Ehigiamusoe (2022) found that education reduces the gender gap and improves financial inclusion. Ozili (2018) argued that digital finance that is offered through Fintech providers has positive effects for financial inclusion because of the convenience that digital finance provides to individuals with low and variable income.…”
Section: Literature Reviewmentioning
confidence: 95%
“…The relationship between education and income gaps is not limited to a linear one but is intertwined with other factors in a spiral. For example, the contribution of agricultural productivity and modernization to higher incomes, and the contribution of gender inequality to financial inequality [7,8]. Not only that, but social security expenditures also have an impact on the urban-rural income and education gap.…”
Section: Multi-perspective Analysismentioning
confidence: 99%
“…Gender equality in access to credit and financial stability (Perrin y Weill, 2022) Gender and financial inclusion: does technology make a difference? (Ghosh, 2022) The role of education in filling the gender gap in financial inclusion in low-income economies (Pahlevan et al, 2022) Narrowing the gender gap in mobile banking (Lee et al, 2022) Digital credit and the gender gap in financial inclusion: Empirical evidence from Kenya (Johnen y Mußhoff, 2022) Financial inclusion and digital banking on an emergent economy (Guerra-Leal et al, 2021) Formal credit usage and gender income gap: the case of farmers in Cambodia (Sam, 2021) Sex, language and financial inclusion (Osei-Tutu y Weill, 2021) Gender disparity in the digitalization of financial services: challenges and promises for women's financial inclusion in India (Kulkarni y Ghosh, 2021) The effect of financial literacy and gender on retirement planning among young adults (García, 2021) Financial kiteracy and intra-household decision making: Evidence from Rwanda (Grohmann et al, 2021) Financial literacy: Thai middle-class women do not lag behind (Grohmann et al, 2021) Stereotypes in financial literacy: Evidence from PISA (Bottazzi y Lusardi, 2021) Gender differences in financial literacy: The role of stereotype threat (Tinghög et al, 2021) Financial literacy among Finnish adolescents in PISA 2018: The role of financial learning and dispositional factors (Silinskas et al, 2021) The financial literacy gender gap and the role of culture (Rink et al, 2021) Gender differences in risky asset behavior: The importance of self-confidence and financial literacy (Cupák et al, 2021) What is good for the goose is good for the gander? : How gender-specific conceptual frames affect financial participation and decision-making (Boggio et al, 2020) Gender income gap in rural informal micro-enterprises: An unconditional quantile decomposition approach in the handloom industry (Hazarika, 2020) Gender differences in financial knowledge, attitudes, and behaviors: Accounting for socioeconomic disparities and psychological traits (Robson y Peetz, 2020) Measuring economic competence of secondary school students in Germany (Kaiser et al, 2020) The interaction effect of gender and ethnicity in loan approval: A Bayesian estimation with data from a laboratory field experiment (Gonzales Martínez et al, 2020) Access to finance -Mind the gender gap (Morsy, 2020) Early causes of financial disquiet and the gender gap in financial literacy: Evidence from College students in the Southeastern United States (Al-Bahrani et al, 2020) Determinants of digital finance in India (Ghosh y Hom, 2020) Does gender...…”
Section: Scopusmentioning
confidence: 99%